2015
DOI: 10.1080/19942060.2015.1066533
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of buoyancy-driven instability for thermohaline stratification in a Hele-Shaw cell and extended geometry

Abstract: Studies on buoyancy-driven instabilities are of considerable interest for its wide application in oceanic, environmental and industrial fields. For miscible two-layer stratifications in a Hele-Shaw cell, the base state density profile in the diffusion regime can be predicted by linear stability analysis such that the buoyancy-driven instabilities can be classified in (R, δ) parameter space, where R is the initial density stability ratio and δ is the diffusion coefficient ratio. However, flow dynamics in extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…8 Recently, we have found that this classification of the convection modes can also be applied to the unbounded thermohaline flow, which does not obey Darcy's law. 9 In this study, we provide a report on the three-dimensional convection structures in the thermohaline stratification with hot salted water located below the cold fresh water, also referred to simply as the salt-heat system. With the rapid development of supercomputer and parallel computing technology, three-dimensional studies on the miscible two-layers flow have attracted more and more interests.…”
Section: -2mentioning
confidence: 99%
See 4 more Smart Citations
“…8 Recently, we have found that this classification of the convection modes can also be applied to the unbounded thermohaline flow, which does not obey Darcy's law. 9 In this study, we provide a report on the three-dimensional convection structures in the thermohaline stratification with hot salted water located below the cold fresh water, also referred to simply as the salt-heat system. With the rapid development of supercomputer and parallel computing technology, three-dimensional studies on the miscible two-layers flow have attracted more and more interests.…”
Section: -2mentioning
confidence: 99%
“…(4) are the reciprocals of the respective values in Ref. 9, because the hot salted water is located below the cold fresh water in this study. The unit vector in the vertical direction is denoted as k. The dimensionless position x, velocity u, pressure p, time τ, temperature T, salinity S, Prandtl number Pr and Rayleigh number Ra T are given by:…”
Section: Mathematical Modelmentioning
confidence: 99%
See 3 more Smart Citations